Da lei de Wagner no Brasil um estudo acerca da validade atual e da aplicaÃÃo - Raimundo Ivan Vieira (2014)
The objective of this work is to identify whether the Wagner Law, which refers to the effect of public spending on economic growth can be observed for the Brazilian reality. According to Wagner, the public sector is able to intervene in the economy to alter its growth trajectory, with such a process promoted by higher expenses. To test the hypothesis Wagner information was collected on the amount of government spending and the Brazilian production between 1909 and 2012, extracted from IPEADATA. The processing of information in order to reproduce the arguments that led to the completion of the verification or not the Wagner Law was based on techniques of time series. The model of Vector Autoregressive (VAR), the analysis of Granger and Cointegration test were used. Still, the tests of Dickey - Fuller and Phillip - Perron test for identification to check the type of behavior that characterizes the best series of public spending and growth were used. The results highlight that both variables have decided not stationary in level, you characterize as well as a process I(1). The impulse response functions showed a positive relationship not spending towards growth and a low explanatory power of the fluctuations of the latter after the first 20 periods, respectively. The test of Granger pointed out that there is a unidirectional relationship between public spending and growth, with the same expenditure towards growth - ie, only growth can affect the spending behavior in the Granger sense. Finally, the cointegration analysis did find arguments in favor of a long-term relationship for the series in question.